Patterns of peasant way of life in Tobolsk province in the second half of the XIXth century (on the materials of N.N. Mataev’s personal archive) - I. S. Ivanchenko (Вестник Майкопского государственного технологического университета, 2024)
The goal of the research is to analyze the specifics of the everyday life of old-timer peasants of Tobolsk province on the basis of information collected during ethnographic fieldwork in the Tyumen region. On the basis of the involved narrative sources, such as personal diaries, memoirs, biographies and retelling of ancestral memories of the hereditary peasant N.N. Mataev, marital behavior, child-parent relations, interaction between family members in and out of the home lifehave been studied, the level of child mortality and birth rate have been analyzed, and the cultural specifics of everyday life of several generations of one family have been revealed. The collected records in the form of interviews, diaries and memoirs refer to the end of the 19th century and the beginning of the 20th century, i.e. to the period of active changes and transformations in the way of life of the peasant village in Russia, which determines the relevance of the research, because a thorough study of the identity of the Siberian sub-ethnos allows us to find differences in the consequences of these transformations and understand the history of Western Siberia. The principle of historicism and the civilizational approach applied allow us to observe the stages of development of new forms of family structure and the transformation of peasant life as a result of modernization. The studied ethnographic materials allow to present more fully the picture of peasant everyday life and to draw conclusions about the specific features of the life cycle of the traditional patriarchal peasant family and the community of old residents of Tobolsk province.